Bovine Helminthosis: Blood Glucose Levels and Age Influence on Susceptibility in Some Nigerian Breeds of Cattle (2015)
The effect of natural bovine helminthosis on blood glucose levels and the influence of age on its susceptibility were studied in four breeds of cattle in Ibadan Nigeria, using abattoir samples. One hundred and twenty cattle (28 males and 92 females) comprising Sokoto Gudali (51),White Fulani (30), Red Bororo (24) and Kuri (15) breeds of cattle which were all above 2.5 years old were used for this study. The blood glucose levels of all the cattle were determined by spectrophotometric method using Randox kitR (Randox LaboratoriesLimited, United Kingdom) while the corresponding fecal samples were examined for the helminth burden using the modified McMaster technique. The age of each cattle was estimated using a standard dentitition technique. The data obtained were subjected to Analysis of Variance (ANOVA) and Correlation analysis. Significance was determined at p< 0.05. Sokoto Gudali breed was the least susceptible (21.56%) to natural helminthosis while Kuri breed was the most susceptible (26.67%). Cattle in age range of 2.5-3years were the most susceptible to natural helminthosis across all the breeds, while cattle older than 3 years were less susceptible. Blood glucose had positive correlation with age (r = 0.24) and negative correlation with helminth burden (r = -0.14). Hypoglycemia was prominent in all the cattle with heavy helminth burdens. Female cattle showed a significantly higher susceptibility to natural helminthosis than males. This study identifies natural helminthosis as a predisposing factor to hypoglycemia in Nigerian breeds of cattle which is observed to be more severe in younger cattle.